Research Progress and Effects of Light on Poultry Circadian Rhythm Regulation Based on CiteSpace - Yue Yu; Zhanming Li (Applied Sciences, 2023)
Light is not only an important environmental regulation factor in poultry growth and development, but it is also a key factor affecting circadian rhythm. To explore research frontiers between light and circadian rhythm, this study analyzes related literature in the field of light and circadian rhythm from the Web of Science core database and draws a knowledge graph using CiteSpace, presenting the subject distribution and research frontiers. This study also focuses on the regulation of light in the circadian rhythm of poultry, explores the effects of light on the growth and immunity of poultry, and analyzes the regulatory effect of light on melatonin levels. In summary, the current research frontiers of light and circadian rhythm are lighting, hepatocytes, the suprachiasmatic nucleus (SCN), blue light, and immune function. Light regimes played important roles in poultry welfare, yield, growth and development and affected the circadian rhythm in poultry by regulating melatonin levels. The exploration of the relationships between clock genes and circadian rhythm was important for the application of light regulation in poultry.